The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.pt.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Integrated Vector Management to promote healthy environments

Abstract: Integrated Vector Management (IVM) strategies are intended to protect communities from pathogen transmission by arthropods. These strategies target multiple vectors and different ecological and socioeconomic settings, but the aggregate benefits of IVM are limited by the narrow focus of its approach; IVM strategies only aim to control arthropod vectors. We argue that IVM should encompass environmental modifications at early stages, for instance, infrastructural development and sanitation services, to regulate n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 54 publications
1
36
0
2
Order By: Relevance
“…With the guidance of administrative cells Community Health Workers (CHWs), the coordinates and the elevation of each breeding site were marked using a hand-held Global Positioning System (GPS), GARMIN etrex 12 CHANNEL (Lizzi et al, 2014) and the land use type identified on each breeding site was described The captured data were later …”
Section: • Data Collectionmentioning
confidence: 99%
“…With the guidance of administrative cells Community Health Workers (CHWs), the coordinates and the elevation of each breeding site were marked using a hand-held Global Positioning System (GPS), GARMIN etrex 12 CHANNEL (Lizzi et al, 2014) and the land use type identified on each breeding site was described The captured data were later …”
Section: • Data Collectionmentioning
confidence: 99%
“…While these tools have yielded significant reductions in malaria transmission, there is a need to identify synergistic combinations of vector control strategies , especially in the face of emerging insecticide resistance . WHO has advocated for an Integrated Vector Management (IVM) strategy, a capacity‐building approach in which multiple interventions, tailored to unique ecological settings , are employed jointly to increase cost‐effectiveness and sustainability .…”
Section: Introductionmentioning
confidence: 99%
“…The strategy encompasses environmental modifications through both infrastructural development and sanitation services, to regulate not only the vectors but also the exposure to mosquito bites. It also seeks to improve public health and quality of life, and to minimise social-disparities (Lizzi et al, 2014). In line with this integrative strategy for malaria elimination, identifying regions of high levels of social vulnerability to malaria can help decision-makers provide tailor-made interventions in the most vulnerable areas of Rwanda.…”
Section: Introductionmentioning
confidence: 99%